AI AND THE EVOLUTION OF POST-DIGITAL ART MOVEMENTS - Muthuraju V,; Saini, Rajat; Khurana, Jatin; Kaushik, Sanchi; Anwa, Syed Rashid (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The evolution of post-digital art experiences paradigm shift of the use of technology by artists not to the novelty of the digital but to a comprehensive critical engagement with the artificial intelligence (AI) as a medium and a collaborator. The paper addresses AI overlap with post-digital art, and traces the historical and theoretical development of the creative systems and the way they shape the creative processes and artistic ideology transformation. The transition between the digital and post-digital culture signified the transition of the technological interest and reflective interaction, the greater emphasis on the hybridity, materiality and symbiosis between the humans and computers. With machine learning and generative algorithms taking over as the main forces behind creativity, AI has become the new center of creativity, spawning such new movements as computational expressionism, interactive installations, or data-driven aesthetics. These activities interfere with the traditional constructs of authorship, originality, and agency of the artwork and lead to the posthumanist perspectives that derail the distinctions between author and work. There are also important cultural and economic consequences of the AI integration into the art world, which have effects on the market, the institutional practice and ethics of creative production. The sustainability, bias and artistic integrity concerns become more pronounced as artists become more involved in working with autonomous systems. Finally, the intersection of AI and post-digital art does not only mark the beginning of the change in technology but also the alteration of the very definition of creativity, that which is regarded as a dialogic between the human intuition and the algorithmic intelligence, and its future.